Madura dan Potensi Wisata Rempah: Kajian Strategi Komunikasi Pemasaran Pariwisata - Suryandari, Nikmah; Rahmawati, Farida Nurul; Adhidharma, Ferry (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2024)
The COVID-19 pandemic has stopped the activities of the global tourism industry. This condition is further exacerbated by the atmosphere of uncertainty and the lack of effective vaccination. This resulted in people starting to try various drugs to boost their immunity, turning to traditional medical practices and alternative medicine. The use of spices in food and herbal medicine is known as one of Madura's tourism potential. This research aims to determine the tourism marketing communication strategy for Madurese spice products. This paper presents a niche tourism sector that emphasizes the potential of spice tourism. The research aims to determine strategies for promoting spice-based tourism and for developing Madura tourism. The research used a qualitative descriptive method with informants from spice-based tourism businesses in Madura. The research results show that the use of tourism marketing communication strategies in Madura uses a 7P marketing mix perspective, namely product, price, place, promotion, people, process, physical evidence.